Cage operated across Athabasca River, operated by Jeff [Coke] and carried as many as 150 passengers a day. (Alice B. Donahue Library & Archives)
Cable cage, Athabasca, Alberta. A note on the back reads: This is the cage they used across the river this fall. Had a different engine than last year and it worked well. Carried four passengers and Jeff Coke the operator. Was running over a month and carried as high as 150 passengers a day. photograph